2012
DOI: 10.1016/j.seizure.2012.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous levetiracetam in acute repetitive seizures and status epilepticus in children: Experience from a children's hospital

Abstract: This observational study has confirmed previous data that intravenous levetiracetam seems to be effective and safe in the treatment of acute repeated seizures and status epilepticus. A randomised clinical trial is justified to determine whether intravenous levetiracetam should replace intravenous phenytoin as the first long-acting anticonvulsant in the management of acute repetitive seizures and status epilepticus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 29 publications
3
40
0
3
Order By: Relevance
“…The drug has since gained broader approvals for treatment of a variety of partial and generalized seizure conditions, including those in pediatric patients 13, 14. Levetiracetam has a therapeutic profile closer to ideal than most other anticonvulsants15 and the parenteral form is now used increasingly to manage cluster seizures and status epilepticus in the very young, elderly, and critically ill humans 16, 17, 18, 19, 20…”
mentioning
confidence: 99%
“…The drug has since gained broader approvals for treatment of a variety of partial and generalized seizure conditions, including those in pediatric patients 13, 14. Levetiracetam has a therapeutic profile closer to ideal than most other anticonvulsants15 and the parenteral form is now used increasingly to manage cluster seizures and status epilepticus in the very young, elderly, and critically ill humans 16, 17, 18, 19, 20…”
mentioning
confidence: 99%
“…Larger cohorts in adult patients basically confirmed an useful riskbenefit ratio of LEV-iv [6,7,19]. Data to support LEV-iv use in children with acute seizures or refractory SE are even more limited, but in case reports and in observational studies LEV-iv has also been reported to be an effective and safe adjuvant therapy in children with refractory SE [20,21]. The established status epilepticus trial (ESET) [22] was designed to compare the use of fos-phenytoin, valproate and levetiracetam regarding their efficacy in treating SE among patients older than 2 years after the use of benzodiazepines, and will possibly add further information to this important topic.…”
Section: Discussionmentioning
confidence: 89%
“…Intravenous preparation has recently shown efficacy in neonatal seizures and status epilepticus [15,16].…”
Section: Levetiracetammentioning
confidence: 99%